Accessorizing the Body : Habits of Being I - Rabinowitz, Paula; Giorcelli, Cristina (Book collections on Project MUSE., 2011)
"The first in the four-part series Habits of Being, charting the social, cultural, and political expression of clothing as seen on the street and in museums, in films and literature, and in advertisements and magazines, this volume features a close-up focus on accessories, the shoe, the hat, the necklace, intimately connected to the body. These essays, most of which have appeared in the cutting-edge Italian series Abito e Identita, offer new theoretical and historical takes on the role of clothing, dress, and accessories in the construction of the modern subject. With contributions by leading scholars in art history, semiotics, literary and film studies, history and fashion studies, and with additional writings by psychoanalysts, textile artists, and fashion designers from Europe and America, readers will encounter a dizzying array of ideas about the modern body and the ways in which we dress it. From perspectives on the model body to Sonia Delaunay's designs, from Fascist-era Spanish women's prescribed ways of dressing to Futurist vests, from Barbara Stanwyck's anklet to Salvatore Ferragamo's sandals, from a poet's tiara to a worker's cap, from the scarlet letter to the yellow star: Accessorizing the Body imparts startling insights into how much the most modest accessory might reveal"--Provided by publisher.